PENGARUH EARNINGS PER SHARE, LOAN TO DEPOSIT RATIO, ARUS KAS OPERASI, DAN RETURN ON EQUITY TERHADAP HARGA SAHAM EMITEN SEKTOR PERBANKAN DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2015)
This study aims to examine and analyze the effect of Earning per share, Loan to Deposit Ratio, Operating Cash Flow and Return on Equity on the stock price of the banking sector in Indonesia Stock Exchange. The population in this study is a banking company that has gone public on the Indonesia Stock Exchange (IDX) for the period 2009-2013. Sampling technique in this study is the use of purposive sampling. The data analysis technique used is multiple linear regression analysis. Based on the test results it can be concluded that : Earning per share has positive effect on stock prices, loan to deposit ratio has no effect on stock prices, Operating Cash Flows no effect on stock price, return on equity has positive effect on stock prices. Keywords: Earnings Per Share, Loan to Deposit Ratio, Operating Cash Flow, Return on Equity and Stock Prices